Understanding of gharar in sale among ACIS students UiTM Puncak Alam / Nur Sabrina Ismail - Ismail, Nur Sabrina (2019)
In Islam, gharar is one of the prohibited elements in the sale. Many scholars have explained this in more detail. Gharar is divided into two types which are gharar fahish (excessive gharar) and gharar yasir (minor gharar). Although there are various opinions on gharar, it can be concluded that as Muslims we should avoid getting involved in the sale of gharar fahish. This study discusses the level of student understanding of gharar in sales. Synonymous students are often involved with online purchases, so this study was conducted to see their level of understanding. The objective of this study was to examine the level of understanding of sales performance among ACIS students UiTM Puncak Alam. Next, to analyze the method of avoiding the gharar element in the sale and to identify the importance of knowing the gharar element in the sale. The method used for this study is a quantitative method which is through a distributed questionnaire. This study also used library research. This study found that ACIS students UiTM Puncak Alam have a good grasp of the gharar element in the sale. Suggestions for improvement for future studies are to expand the respondents and to increase the objective of the study. Efforts to increase student understanding of the gharar element in the sale can be made by various parties such as the government, teachers, and students themselves.